Growing up Quechua: Ethnic identity, narrative, and the cultural politics of childhood migration in Cusco, Peru. (August 2013) - Hill, Michael Douglas
Drawing from life history interviews with transnational indigenous intellectual Gina Maldonado, of Cusco, Peru, this article examines how Andean children are in motion not only in terms of migration but also across cultural contexts and boundaries that reshape and transform their subjectivities. It also demonstrates the usefulness of life history methods for childhood studies. Processes of movement relationally reconfigure the most salient aspects of racial and class identities and how they are remembered and reconstituted across space and time. From her rural Quechua village, Gina migrated to Cusco for her education, back to the campo (countryside) as a primary schoolteacher, and later to the US to hold visiting university positions teaching Quechua. Her memories of regional childhood migrations emphasize the temporal dimensions and cultural complexities of how Andean ethnic identities are constructed, enacted, and narrated, particularly how educational and religious institutions both facilitated social mobility and yet were sites for the continued fixing of racial and class hierarchies.